Violación constitucional a los derechos de los empleados en los trámites administrativos de inspección integral en la inspectoría provincial de trabajo de El Oro, en el año 2013. Propuesta de reforma al art. 629 del código del trabajo. - Rosero Pereira, Luis Stalin (2014)
Administrative processes of comprehensive inspections that are labor inspectors are procedures whose nature the control that employers' obligations are met. Therefore, they conduct inspections where required documentation supporting compliance with labor-management obligations.